2013
DOI: 10.1186/1471-2229-13-217
|View full text |Cite
|
Sign up to set email alerts
|

New stable QTLs for berry weight do not colocalize with QTLs for seed traits in cultivated grapevine (Vitis vinifera L.)

Abstract: BackgroundIn grapevine, as in other fruit crops, fruit size and seed content are key components of yield and quality; however, very few Quantitative Trait Loci (QTLs) for berry weight and seed content (number, weight, and dry matter percentage) have been discovered so far. To identify new stable QTLs for marker-assisted selection and candidate gene identification, we performed simultaneous QTL detection in four mapping populations (seeded or seedless) with various genetic backgrounds.ResultsFor berry weight, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 75 publications
9
120
0
Order By: Relevance
“…It is generally accepted that berry dimensions are directly affected by seed number at a intragenotypic level (Walker et al 2005), but it is not that obvious at an intergenotypic level Tello et al 2015). In this regard, Doligez et al (2013) have indicated the lack of colocalization between QTLs for berry and seed traits, suggesting that the genetic control of both traits may be partly dissociated.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that berry dimensions are directly affected by seed number at a intragenotypic level (Walker et al 2005), but it is not that obvious at an intergenotypic level Tello et al 2015). In this regard, Doligez et al (2013) have indicated the lack of colocalization between QTLs for berry and seed traits, suggesting that the genetic control of both traits may be partly dissociated.…”
Section: Resultsmentioning
confidence: 99%
“…Microsatellite and SNP markers have become in the last years the markers of choice for genetic analyses in grapevine, including genetic mapping and QTL identification (Huang et al 2012;Doligez et al 2013;Battilana et al 2013;Barba et al 2014), linkage disequilibrium and association analyses (Emanuelli et al 2010;Barnaud et al 2010;Cardoso et al 2012;Vargas et al 2013), and varietal identification (Myles et al 2010;Cabezas et al 2011;Laucou et al 2011;Migliaro et al 2012). As in many other woody plant species, genetic mapping in grapevine has been carried out using mainly the double pseudo test-cross strategy (Grattapaglia et al 1995), which is based on the study of allelic segregation of markers found in heterozygosis in one or both progenitors of an F 1 progeny.…”
Section: Applications Of the Developed Multiplex Pcrsmentioning
confidence: 99%
“…The availability of the grapevine genome sequence combined with the advent of cheaper and high throughput single nucleotide polymorphism (SNP) genotyping strategies (Gupta et al 2008;Davey et al 2011) were expected to shift the tools of genetic studies in grapevine. However, microsatellites are still the predominant markers contributing to the current knowledge of genetic determinism of the major grapevine traits (Mejía et al 2011;Huang et al 2012;Duchêne et al 2012;Karaagac et al 2012;Doligez et al 2013;Battilana et al 2013;Grzeskowiak et al 2013;Ban et al 2014;Correa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing polymorphic regions between seedless (AR and TS) vs. seeded (It and RG) and big berry vs. small berry (TS) varieties, we were able to identify polymorphisms in genes involved in hormone responses and metabolism in berry growth as putative candidate genes. For example the gene coding for the Auxin Response Factor 5 (ARF5) showed a higher CN in the TS genome and was recently mapped to a quantitative trait locus associated to berry weight and traits [22]. Likewise we found polymorphisms specific to the seedless varieties with respect to the seeded ones in genes involved in transport overview pathways, such as PIP2B, which codes a member of the aquaporin gene family.…”
Section: Polymorphic Genesmentioning
confidence: 83%